Discharge of Meteoric Water in the Eastern Norwegian Sea since the Last Glacial Period. Issue 14 (19th July 2019) - Hong, Wei‐Li; Lepland, Aivo; Himmler, Tobias; Kim, Ji‐Hoon; Chand, Shyam; Sahy, Diana; Solomon, Evan A.; Rae, James W. B.; Martma, Tõnu; Nam, Seung‐Il; Knies, Jochen
Abstract: Submarine groundwater discharge could impact the transport of critical solutes to the ocean. However, its driver(s), significance over geological time scales, and geographical coverage are poorly understood. We characterize a submarine groundwater seep from the continental slope off northern Norway where substantial amount of meteoric water was detected. We reconstruct the seepage history from textural relationships and U‐Th geochronology of authigenic minerals. We demonstrate how glacial‐interglacial dynamics have promoted submarine groundwater circulation more than 100 km offshore and result in high fluxes of critical solutes to the ocean. Such cryosphere‐hydrosphere coupling is likely common in the circum‐Arctic implying that future decay of glaciers and permafrost in a warming Arctic is expected to attenuate such a coupled process and thus decreases the export of critical solutes. Plain Language Summary: Occurrence of meteoric groundwater (freshwater originated from precipitation such as rain and snow) in the global ocean is an unexpected but seemingly common phenomenon. Here, we report evidence for meteoric groundwater flow at 800‐m water depth from the coast of northern Norway. Dating of the chemically formed carbonate rocks on the seafloor, an oxidation product of methane, reveals that the groundwater flow was strongest when large ice sheets occupied the nearby shelf. Our results confirm the temporal and geographical scales of meteoric groundwater flow in the Arctic region and highlight its impact on carbon cycling and ocean chemistry. Key Points: We document the connection between glacial dynamics and the discharge of meteoric water from the eastern Norwegian Sea A large quantity of critical solutes discharge to the ocean as a result of water circulation Offshore presence/discharge of freshwater is a common phenomenon in the circum‐Arctic Ocean that have profound impact on ocean chemistry